2021
DOI: 10.3389/fimmu.2021.779235
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 7 Regulates Nitric Oxide Production and Apoptosis to Promote Mycobacterial Clearance in Macrophages

Abstract: The host immune system plays a pivotal role in the containment of Mycobacterium tuberculosis (Mtb) infection, and host-directed therapy (HDT) is emerging as an effective strategy to treat tuberculosis (TB), especially drug-resistant TB. Previous studies revealed that expression of sirtuin 7 (SIRT7), a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase, was downregulated in macrophages after Mycobacterial infection. Inhibition of SIRT7 with the pan-sirtuin family inhibitor nicotinamide (NAM), or by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In fact, the signaling pathways and biological processes associated with innate immune responses are highly conserved in Drosophila and vertebrates. For instance, nuclear factor-kappa B (NF-kB) signaling, phagocytosis and apoptosis are evident in the innate immunity of both vertebrates and invertebrates (4)(5)(6)(7)(8). Hence, it is possible to utilize insect models such as flies and nematodes to investigate pathogen and host interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the signaling pathways and biological processes associated with innate immune responses are highly conserved in Drosophila and vertebrates. For instance, nuclear factor-kappa B (NF-kB) signaling, phagocytosis and apoptosis are evident in the innate immunity of both vertebrates and invertebrates (4)(5)(6)(7)(8). Hence, it is possible to utilize insect models such as flies and nematodes to investigate pathogen and host interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined all sirtuin factors ( Supplementary Figure S5 ) and found that only Sirt7, reduced by prior LPS stimulation, was significantly increased in abundance under hesperetin supplementation. Previous studies have demonstrated that Sirt7 can regulate inflammation, OS, and apoptosis, and its beneficial effects have been reported in the vascular endothelium and many other cardiovascular models [ 37 , 38 , 39 ]. However, the role of Sirt7 in CAVD is incompletely understood, and the relationship between Sirt7 and Nrf2 remains undefined.…”
Section: Resultsmentioning
confidence: 99%
“…Another study described the critical role of caspase-8 in driving the cell death of M.tb -infected mouse macrophages and the control of infection in mice by enhancing apoptosis through the use of specific treatments [ 9 ]. Sirtuin 7 was another factor described to help control M.tb growth through NO-induced apoptosis in RAW 264.7 cells [ 10 ]. There has also been an increasing interest in studying the function of different microRNAs in the context of programmed cell death [ 76 , 77 , 78 , 79 , 80 ].…”
Section: Cellular Pathwaysmentioning
confidence: 99%